Die Zerstörung von Städten in der Darstellung griechischer epideiktischer Epigramme - Scheithauer, Andrea (Hyperboreus, 2020)
Since wars and catastrophes often threatened the living space of people in antiquity, even the authors of epideictic epigrams lamented the destruction of towns, its causes and consequences. It was probably ﬁrsthand experience of the devastation of Corinth in 146 BC that inspired the ﬁrst expressions of grief over such calamities. Afterwards comments increased during the Augustan period and then later in the 6th century AD. Although many villages were repeatedly aﬄicted by catastrophes, the laments of the epigrammatists concentrated on a few cities, which were destroyed during war. The poets especially were impressed with the fall of Troy. During the reign of Augustus contemporary epigrammatists who were dependent on senators or the patronage of the emperor were interested in this event because of its importance to the gens Iulia. Mostly they combined their lamentations about the cities’ destruction with further reﬂections on the helpless human life and the changes of fortune. On the other side poets rarely treated calamities brought about by natural disasters like earthquakes and ﬂoods. As they dealt with central aspects of the self-representation of cities, the epideictic epigrams are important testimonies of Greek thinking.